Reverse myocardial remodeling according to cardiac magnetic resonance imaging in patients with heart failure and atrial fibrillation receiving dapagliflozin - K. M. Saipudinova; T. M. Uskach; M. A. Sharia; D. V. Ustyuzhanin; S. N. Tereshchenko (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To determine the effect of dapagliflozin on cardiac remodeling parameters and left ventricular mass according to cardiac magnetic resonance imaging in patients with heart failure (HF) with reduced ejection fraction (EF) and atrial fibrillation (AF).Material and methods. The study included 60 patients with HF and AF receiving triple therapy for heart failure for at least 3 months, which were divided into two groups. Patients in the first group (1) were prescribed dapagliflozin, while patients in the second group (2) formed the comparison group. The study analyzed the following cardiac remodeling parameters and left ventricular (LV) mass measured using cardiac magnetic resonance imaging at baseline and after 6 months.Results. Dapagliflozin led to a significant increase in LVEF from 29±6 (27-31) to 37±9 (33-40)% (p<0,001), and a decrease in the volumetric and linear dimensions of the LV and left atrium as follows: end-diastolic dimension from 70 (64-73) to 63 (60-70) mm (p<0,001), end-systolic dimension from 55±7 (52-58) to 50±7 (47-52) mm (p<0,003), end-diastolic volume from 239±50 (220-258) to 207±43 ml/m2 (191-223) (p<0,001), end-systolic volume from 170±40 (155-185) to 140±33 ml/m2 (p<0,001), left atrium from 48±5 (46-49) to 44±6 (42-46) mm (p<0,001), and a decrease in LV mass from 156,5 (130-180) to 109 (98-145) g (p=0,001).Conclusion. In patients with HF with reduced LVEF and AF, dapagliflozin therapy promotes reverse myocardial remodeling processes and increases cardiac contractility.